Does 'gender' mediate or moderate the relationship between 'quality of work life' and 'organizational commitment'?: Evidence from SMEs in Egypt. Issue 4 (19th April 2018) - El Badawy, Tarek A.; Chinta, Ravi; Magdy, Mariam M.
Abstract : Purpose: Literature on organizational commitment of employees has long established that quality of work life (QWL) is a significant determinant. However, the strength of the relationship between organizational commitment and QWL is more complicated given the diversity of employees and the broad scope of organizational commitment as a construct. The researchers break down organizational commitment into three distinct measures as extant literature suggests and then explore the role played by gender in a culturally rich context as in Egypt. Design/methodology/approach: This paper is based on a sample of 117 respondents from small and medium enterprises (SMEs). Items used in the survey were extracted from previous research studies. The survey consisted of 39 questions to measure the three research variables. QWL was measured using Zin's (2004) developed questionnaire. The items covered seven dimensions: growth and development, participation, physical environment, supervision, pay and benefits, social relevance and workplace integration. The reported Cronbach's alpha for the scale was 0.93. Items were measured on a five-point Likert scale. Findings: The researchers empirically found that gender plays only a minor and moderating role in the relationship between QWL and affective commitment. The researchers conclude the study with implications for policy, practice and future research. Research limitations/implications: This study had several limitations. First, the sample size was relatively small. Second, the sample composition (singular focus on SMEs in Egypt) was not diverse enough. Third, the tools used in collecting the data were not adjusted to the national cultural context. Fourth, the study lacks an experimental design which is a limitation (Shadish et al., 2002). These limitations, taken together, limit the generalizability of the results and conclusions from the study. Thus, the results are suggestive rather than definitive. Additionally, only the association between variables was investigated, and the researcher did not clearly explore the cause–effect relationships. Whether QWL is the antecedent or the consequence is another research question yet to be explored. Practical implications: It is recommended for future researchers to enlarge and diversify the sample. Additional investigations of the role of gender as a mediator or moderator need to be explored. Researchers should also study the roles of other demographic variables to highlight behavioural and attitudinal variables that significantly affect QWL. Originality/value: While the primary relationship between "perceived quality of work life" and "organizational commitment" is well established in existing literature across many organizational contexts, there is a paucity of research on the moderating and/or mediating effects of third attitudinal variables on this primary relationship. Hence, the main focus of this study was to empirically test the moderating and/or mediating effects of gender on the relationship between "perceived quality of work life" and "organizational commitment." The researchers examine organizational commitment more granularly in terms of its components, namely, affective, continuance and normative commitments.